2020
DOI: 10.3390/biomedicines8090318
|View full text |Cite
|
Sign up to set email alerts
|

Co-Microencapsulation of Islets and MSC CellSaics, Mosaic-Like Aggregates of MSCs and Recombinant Peptide Pieces, and Therapeutic Effects of Their Subcutaneous Transplantation on Diabetes

Abstract: The subcutaneous transplantation of microencapsulated islets has been extensively studied as a therapeutic approach for type I diabetes. However, due to the lower vascular density and strong inflammatory response in the subcutaneous area, there have been few reports of successfully normalized blood glucose levels. To address this issue, we developed mosaic-like aggregates comprised of mesenchymal stem cells (MSCs) and recombinant peptide pieces called MSC CellSaics, which provide a continuous release of angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our study showed that 3D spheroid formation significantly increased the secretion and mRNA levels of TGF-β, as well as activated the TGF-β/Smad signaling pathway in SHED. The increased immunomodulatory activity of human MSCs in spheroids may be attributed to enhanced intercellular adhesions and cell contactdependent signaling, which have also been associated with the heightened paracrine activity of MSC aggregates [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that 3D spheroid formation significantly increased the secretion and mRNA levels of TGF-β, as well as activated the TGF-β/Smad signaling pathway in SHED. The increased immunomodulatory activity of human MSCs in spheroids may be attributed to enhanced intercellular adhesions and cell contactdependent signaling, which have also been associated with the heightened paracrine activity of MSC aggregates [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, mesenchymal stem cells (MSCs) can release soluble cytokines and growth factors to neighboring cells to suppress the immune response, resulting in no local immunosuppression for MS [ 33 ]. In this context, MSCs and islet cells were simultaneously encapsulated into alginate hydrogel to improve the survival rate of the transplanted islet cells, promoting insulin secretion and new blood vessel formation [ 34 , 35 ].…”
Section: Islet Encapsulationmentioning
confidence: 99%
“…They form 100-150 µm-sized pseudoislets with high survival rate and good glucose-stimulated insulin secretion and revealed the improvement of the endocrine function of diabetic animals by transplantation [79]. Recently, Kogawa, Mochizuki, and colleagues showed that the encapsulation technique using human recombinant collagen I (Cellsaic) with mesenchymal stem cells contributed to the improvement of transplant efficacy of islet xenotransplantation by promoting angiogenesis [80,81].…”
Section: New Strategy For Improving Islet Transplantation Using Collagenmentioning
confidence: 99%